UMA ANÁLISE SOBRE PRÁTICAS EDUCATIVAS INCLUSIVAS NO ENSINO SUPERIOR À LUZ DO DESENHO UNIVERSAL PARA APRENDIZAGEM - Samantha Ferreira da Costa Moreira (2023)
The main objective of this work consisted of identifying the use of inclusive educational practices in general, and their relationship with the UDL perspective in particular, in the classes of a Medicine course in the Brazilian Midwest region. For this, we carried out a documental analysis of the Pedagogical Project of the Course (PPC), of the teaching plans of course disciplines and of a structured questionnaire answered by effective professors. We relate these inclusive educational practices of the plans and the classes taught by these teachers with practices specific to Universal Design for Learning. Before these analyses, we discussed aspects and the context of inclusion in Brazil and in the world, trying to find a point of confluence between inclusive proposals and inclusive practices in Higher Education. We found in the legislation only proposals for basic education, but, unfortunately, there is not a diversity of inclusive educational practices with the Higher Education public as its main focus. For the theoretical basis of the work, we discussed, without the objective of exhausting the subject, about the Universal Design (UD) for Learning and we also carried out a discussion about pedagogical practices from an inclusive perspective through the UDL, more specifically, about the planning, the teaching methodologies and also on learning assessment resources and processes. We conclude that there is still much to be thought, discussed and done related to the theme of Inclusive Education in Higher Education, mainly in the policy of teacher training, as these will replicate the acquired knowledge, spreading and expanding ideas, methods and techniques that will certainly consolidate inclusive education in Brazil. We concluded, in our specific analysis in the Medicine course, that most of the professors empirically use, without any method rigor, ideas of inclusive education in their plans and classes and that the PPC was built under some inclusive ideas, mainly regarding the regulatory bases and the National Curriculum Guidelines (DCN's) for the course, as well as the methodological proposals and some disciplines and/or contents that can be considered inclusive, but in the PPC they appear only as general strategies. From all of this, we conclude that inclusive ideas and strategies, even from the DUA, exist in this course, but there is a lack of this specific look at diversity and an explanation aimed at serving everyone, including those who may have deficiencies.